The extreme properties of the nearby hyper-Eddington accreting active galactic nucleus in IRAS 04416+1215. Issue 3 (30th October 2021) - Tortosa, Alessia; Ricci, Claudio; Tombesi, Francesco; Ho, Luis C; Du, Pu; Inayoshi, Kohei; Wang, Jian-Min; Shangguan, Jinyi; Li, Ruancun
ABSTRACT: The physical properties of the accretion flow and of the X-ray emitting plasma, in supermassive black holes accreting at extreme Eddington rates, are still very unclear. Here we present the analysis of simultaneous XMM–Newton and NuSTAR observations of the hyper-Eddington Seyfert 1 galaxy IRAS 04416+1215, carried out in 2020. The main goal of these observations is to investigate the properties of the X-ray corona, as well as the structure of the accretion flow and of the circumnuclear environment, in this regime of extreme accretion. IRAS 04416+1215 has one of the highest Eddington ratio (λEdd ≃ 472) in the local Universe. It shows an interesting spectral shape, very similar to the standard narrow-line Seyfert 1 galaxy's spectra, with the presence of multiphase absorption structure composed of three phases, whose estimate of the minimum and maximum distances suggests two different interpretations, one consistent with the three X-ray winds being cospatial, and possibly driven by magnetohydrodynamical processes, the other consistent with the multiphase winds being also multiscale. The X-ray spectrum of IRAS 04416+1215 also has a prominent soft excess component and a hard X-ray emission dominated by a reflection component. Moreover, our detailed spectral analysis shows that IRAS 04416+1215 has the lowest coronal temperature measured so far by NuSTAR ( kT e = 3–22 keV, depending on the model). This is consistent with a hybrid coronal plasma, in which the primary continuum emission is driven by pair production due to high-energy tail of the energy distribution of non-thermal electrons.